THE EFFECT OF GOAT MANURE FERTILIZER COMBINED WITH ACTIVED CHARCOAL ON GROWTH AND YIELD OF KEMBANG TELANG (Clitoria ternatea L.) - I K. A., Sumarjana; Roni, N. G. K.; Witariadi, N. M. (Jurnal Peternakan Tropika, 2023)
This study aimed to determine the effect of goat manure fertilizer combined with actived charcoal on growth and yield of kembang telang (Clitoria ternatea L.). The research was conducted at the Greenhouse, Sesetan Research Station, Faculty of Animal Husbandry, Udayana University. The study lasted for 8 weeks, using a completely randomized design (CDR) with 7 treatments and each treatment was repeated four times, so there were 28 experimental units. The treatmens were goat manure fertilizer (KK) and actived charcoal (AA) were D0: 0 ton ha-1, D1: 10 ton ha-1 KK, D2: 20 ton ha-1 KK, D3: 30 ton ha-1 KK, D4: 5 ton ha-1 KK + 5 ton ha-1 AA, D5: 10 ton ha-1 KK + 10 ton ha-1 AA, D6: 15 ton ha-1 KK + 15 ton ha-1 AA. Variables measured in this experiment were growth, yield, and plant growth characteristic variables. The treatment of 15 ton ha-1 KK + 15 ton ha-1 AA dosage (D6) increased all variables except number of leaves and growth characteristic of Clitoria ternatea L. It can be concluded that combination 15 ton ha-1 of goat manure fertilizer with 15 ton ha-1 activated charcoal dosage treatment given best growth and yield of Clitoria ternatea L. Key words: activated charcoal, clitoria ternatea, Goat manure fertilizer, growth, yield